How Pedagogy 2.0 Can Foster Teacher Preparation and Community Building in Special Education - Hardman, Elizabeth (Social Inclusion, 2015)
This paper describes how one teacher educator used action research methodology to investigate the feasibility of using Web 2.0 technology to build a virtual professional learning community (PLC) in special education to support the preparation of highly qualified special education teachers. Study participants included 218 pre-service and in-service teachers who joined the virtual PLC over a four-year period. Data were collected using two Web 2.0 tools, wiki and Ning, and analyzed to evaluate the degree to which the virtual community met the essential characteristics of a PLC. The results showed that 200 of the 218 graduate students who joined the PLC as graduate students continued their membership after graduation but participated in community work as observers only, rarely if ever contributing anything to community growth and development. The implication of the results are discussed with respect to the importance of preparing teachers for service in today’s modern 21st Century academically diverse, inclusive learning communities.